Selection Of Pure Lines Of Mentik Susu Variety Through Participatory Plant Breeding in The Karangnangka Farmers Group, Banjaranyar Village, Pekuncen District, Banyumas Regency: Seleksi Galur Murni Varietas Mentik Susu Melalui Pemuliaan Partisipatif Di Kelompok Tani Karangnangka Desa Banjaranyar Kecamatan Pekuncen Kabupaten Banyumas - Agus Riyanto; Nur Kholida Wulansari; Rifki Andi Novia; Dumaris Priskila Purba (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
The Karangnangka Farmers Group is in Banjaranyar Village, Pekuncen District, Banyumas Regency. This Farmers Group conducts organic rice farming using the Mentik Susu variety. The seeds of this variety are used from generation to generation, so that problems arise, the purity of rice seeds. The solution to this problem is the application of pure line selection through participatory plant breeding. Activities carried out in pure line selection through participatory breeding methods for seed purification are socialization of seed purification activities; planting mixed populations of generation 0; planting superior genotypes in rows; and evaluation of activities. The results of this activity show an increase in knowledge and understanding of Karangnangka Farmers Group farmers regarding pure line selection and obtaining pure superior genotypes of the Mentik Susu variety.